1994
DOI: 10.2169/internalmedicine.33.569
|View full text |Cite
|
Sign up to set email alerts
|

Goodpasture's-Like Syndrome and Effect of Extracorporeal Membrane Oxygenator Support.

Abstract: A 49-year-old man was admitted because of general fatigue, cough and hematuria. During the hospital course, acute renal failure, hemoptysis and dyspnea developed. A percutaneous renal biopsy revealed a diffuse crescentic glomerulonephritis, and direct immunofluorescence showeda linear pattern ofIgG along the glomerular basement membrane. Although serum anti-glomerular basement membrane (anti-GBM) antibody was not detected, Goodpasture's-like syndrome was suspected, and methylprednisolone pulse therapy and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…According to 2 case studies that administered nafamostat mesilate instead of heparin as an anticoagulant to treat pulmonary hemorrhage during ECMO use, Daimon et al (10) and Kotani et al (11) used a nafamostat mesilate infusion rate of 1.0 mg/kg/hr and 1.0-1.7 mg/kg/hr, and ACT was maintained at 150 sec in a 49-yr-old male patient and 190-200 sec in a 27-yr-old female patient, respectively. Nagaya et al (8) successfully treated bleeding complications in 12 neonates on ECMO by administering nafamostat mesilate at 0.48 mg/kg/hr and heparin at 21.0 U/kg/hr, while ACT was maintained at 205.7 sec.…”
Section: Discussionmentioning
confidence: 99%
“…According to 2 case studies that administered nafamostat mesilate instead of heparin as an anticoagulant to treat pulmonary hemorrhage during ECMO use, Daimon et al (10) and Kotani et al (11) used a nafamostat mesilate infusion rate of 1.0 mg/kg/hr and 1.0-1.7 mg/kg/hr, and ACT was maintained at 150 sec in a 49-yr-old male patient and 190-200 sec in a 27-yr-old female patient, respectively. Nagaya et al (8) successfully treated bleeding complications in 12 neonates on ECMO by administering nafamostat mesilate at 0.48 mg/kg/hr and heparin at 21.0 U/kg/hr, while ACT was maintained at 205.7 sec.…”
Section: Discussionmentioning
confidence: 99%
“…Initial improvement and weaning from ECMO has been reported in an adult patient with Goodpasture’s-like pulmonary-renal syndrome, who subsequently died after rebleeding 36. There are at least seven case reports of VV ECMO applied to adults with acute refractory respiratory failure secondary to Wegener’s granulomatosis, most of which had severe preexisting pulmonary hemorrhage 11,18–22,37…”
Section: Discussionmentioning
confidence: 99%
“…Nafamostat mesylate as anticoagulant is also rarely reported 31,36. Heparin infusion to maintain an ACT of 160–1804,5 or 130–150 seconds (instead of the institutional standard of 180–220) and a modified ECMO circuit with two oxygenators placed in parallel (one primed in-line to allow quick change in case of clotting)9 have been reported in pediatric patients with pulmonary hemorrhage due to GPA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Daimon et al 15 reported a patient with pulmonary hemorrhage due to Goodpasture's-like syndrome who died of pulmonary rebleeding 17 h after ECMO disconnection. In this case, although oxygenation improved remarkably during ECMO support, the autopsy revealed that the lung was not reformed.…”
Section: Discussionmentioning
confidence: 99%